2019
DOI: 10.1177/0964528419887978
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of acupuncture for pain reduction in delayed-onset muscle soreness: a systematic review

Abstract: Objective: The aim of this study was to systematically review the literature on acupuncture for delayed-onset muscle soreness (DOMS) and report upon study quality and treatment outcomes. Design: Systematic review. Data sources: Searches were conducted in the following electronic databases from their inception to 31 March 2018: CINAHL, MEDLINE, Allied and Complementary Medicine (AMED) and SPORTDiscus. Reference lists of all included studies and relevant reviews were hand-searched for additional studies. Eligibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…However, there are methods with lack of scientific evidence of their effectiveness or contradictory data. The first group includes kinesiotaping, contrast baths, and acupuncture [ 13 , 14 , 15 , 16 , 17 , 18 ]. The second group of methods most likely includes cyclic compression therapy, stretching, general cryotherapy, and sauna use [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are methods with lack of scientific evidence of their effectiveness or contradictory data. The first group includes kinesiotaping, contrast baths, and acupuncture [ 13 , 14 , 15 , 16 , 17 , 18 ]. The second group of methods most likely includes cyclic compression therapy, stretching, general cryotherapy, and sauna use [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…O'Connor and Hurley ( 2003 ) systematic review investigated the effectiveness of many physiotherapy interventions (including acupuncture) on DOMS and found no evidence to support that acupuncture helped reduce DOMS, but there were only two trials included in the review. Recently, another systematic review based on more randomized controlled trial (RCTs) (which were not pooled into a meta-analysis) indicated that the therapeutic effect of acupuncture analgesia in DOMS is conflicting (Ko and Clarkson, 2019 ). Therefore, this systematic review and meta-analysis aimed to update the current evidence to evaluate the effects of acupuncture intervention on reducing DOMS and improving muscle performance after strenuous exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise Induced muscle damage (EIMD) following strenuous unaccustomed exercise is common among recreational and professional athletes (1). It may be complicated by the development of delayed onset muscle soreness (DOMS) which may require a few minutes and up to one week recovery time depending on damage severity, and exercise duration and intensity (2,3). DOMS is associated with reduced performance and increased athletes" absenteeism from games.…”
Section: Introductionmentioning
confidence: 99%